FIELD OFFICERS' ADAPTATION TO LABOUR ADMINISTRATION ELECTRONIC CASE MANAGEMENT SYSTEM IN SRI LANKA (Proceedings of the International Conference on Social Sciences, 2024)
Adapting an information system by its intended users is compulsory for the success of that information system. This study focuses on the Labour administration, one of the most critical public functions in any country that secures enforcing the legal provisions relating to work conditions and workers' protection. Labour Administration Electronic Case Management System (LAECMS) is an information system that facilitates labour administration. LAECMS helps and aids field officers in their routine inspection activities. Although, the problem is that field officers' adaptation level is considerably low towards LAECMS in Sri Lanka. That is the motivation behind this systematic review to find associations between the most widely affected characteristics and adaptation. Most of the currently published literature only discusses system-side adaptation. This study bridges the gap by prioritizing user-side adaptation and considering the relevant characteristics. This study relied on a sample of 220 field officers of the Department of Labour (DoL) Sri Lanka. This research investigates the associations between seven primary factors extracted through the reviewed relevant literature and adaptation by using mainly non-parametric tests. The findings of the analysis revealed that digital competency, senior management support, legal framework, user training, perceived usefulness, and perceived ease of use associated with field officers’ adaptation to LAECMS. Among the investigated determinants, user training and perceived usefulness appear to have the most significant association with adaptation. Among them, the impact was strongest in perceived usefulness. Nevertheless, the field officers’ age, gender, and work experience did not associate with their adaptation to LAECMS. The findings of this study would be helpful for the labour law enforcing institutes in any country to understand the successful adaptation to LAECMS has its advantages for the organization as well as for the field officers.
Keywords: information system; adaptation; field officers; electronic case management system; ECMS; labour administration